2006
DOI: 10.1177/0021943606291705
|View full text |Cite
|
Sign up to set email alerts
|

Graduating Students' Responses to Recruitment Advertisements

Abstract: Many firms spend substantial resources in their efforts to recruit the best graduates, and recruitment advertisements can be a critical medium for potential employees deciding on whether to apply for jobs. It is important, therefore, that recruitment advertisements attract the attention of potential applicants and encourage them to apply. The purpose of this study was to examine the variables that influence attention to advertisements and the intention to apply for advertised positions among final-year commerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 33 publications
1
23
0
7
Order By: Relevance
“…Recruitment has always been regarded strategically important to the success of a company, and hence has received considerable academic attention in the field of management (for a review, see Breaugh & Starke, 2000). Recruitment advertising, historically the most commonly used tool for approaching potential employees (Martin, 1987), has also been widely discussed in terms of its effectiveness and impact (Blackman, 2006;Kaplan, Aamodt, & Wilk, 1991;Mathews & Redman, 2001;Roberson, Collins & Oreg, 2005). Literature on the communicative effectiveness of job advertisements has also emerged from the field of marketing (Rai & Kothari, 2008;Ryan, Gubern, & Rodriguez, 2000).…”
Section: Recruitment and Job Advertisementsmentioning
confidence: 99%
“…Recruitment has always been regarded strategically important to the success of a company, and hence has received considerable academic attention in the field of management (for a review, see Breaugh & Starke, 2000). Recruitment advertising, historically the most commonly used tool for approaching potential employees (Martin, 1987), has also been widely discussed in terms of its effectiveness and impact (Blackman, 2006;Kaplan, Aamodt, & Wilk, 1991;Mathews & Redman, 2001;Roberson, Collins & Oreg, 2005). Literature on the communicative effectiveness of job advertisements has also emerged from the field of marketing (Rai & Kothari, 2008;Ryan, Gubern, & Rodriguez, 2000).…”
Section: Recruitment and Job Advertisementsmentioning
confidence: 99%
“…keep the brand salient) (Romaniuk, Peach, Driesener and Sharp 2004;. HRM literature similarly suggests applicants, having diverse needs and interests (Ehrhart and Ziegert 2005), seek demonstration by organisations of their "fit" with the organisation (Rafaeli 2006) through persuasive marketing communication (Blackman 2006). Both literatures recognise the importance of advertising for communicating information about the brand/organisation, building a bond between brand/organisation and customer/applicant (Ehrhart and Ziegert 2005;Feldman, Bearden and Hardesty 2006;Jain and Jain 2005;Kennedy and Ehrenberg 2000).…”
Section: Background and Literaturementioning
confidence: 99%
“…Human Resource Management (HRM) literature has taken some steps to identify job attribute preferences (Konrad, Ritchie, Lieb and Corrigall 2000), to understand the role of specific job attributes in attracting and retaining rural health professionals (Pathman, Konrad, Dann and Koch 2004) and to recommend how best to use classified advertisements to attract job candidates (Blackman 2006). Hemphill, Dunn, Barich and Infante (2007) suggested that integrating these HRM findings with a marketing perspective might be a productive avenue for resolving the GP problem.…”
Section: Introductionmentioning
confidence: 99%
“…Tsai and Yang (2010) stated Organizational attraction as willingness of candidates to seek after occupations and to acknowledge employment offers in an organization. The decision of potential applicants to apply for a job could be affected by the source/medium of recruitment (Blackman, 2006). Hoye and Lievens (2005) explain that recruitment-related data sources and their characteristics can be essential forerunners of organizational attractiveness.…”
Section: Introductionmentioning
confidence: 99%